Два нових салтово-маяцьких кремаційних могильники навколо с. Суха Гомільша на Харківщині - Голубєв, А.М. (Археологія, 2017)
До наукового обігу вводяться два нових салтово-маяцьких могильники за обрядом кремації, відкриті розвідками 2013 р., та поховальні комплекси, що виявлені на них. Presented to scientific circlesis an information on two new Saltiv-Mayaky burial grounds with cremations(Sukha Homolsha Gully and Plaskyi Ravine) discovered in Verkhniy Donets River upper region in Zmiyiv Region of Kharkiv Oblast. Archaeological prospecting in 2013 and 2016 showed that both burial grounds are almost completely destroyed by modern diggers. Plaskyi Ravine burial ground is comparable with its size with the known Sukha Homolsha burial ground with cremations. Archaeological prospecting also showed that the latter site has its extension and can’t be perceived as fully studied. Sukha Homolsha Gully burial ground is at least ten times larger than the one at Plaskyi Ravine. A cache and a cremation in pit were discovered in trenches 1 and 2 correspondingly at Sukha Homolsha burial ground. The burial was traced on an area 0,75 by 0,35 m and was recorded at a depth 0,3 m from the ground surface. The edges of the burial pit were not traced with the archaeological methods. This fact probably testifies that the burial was made on the original surface: bones and funeral goods were just poured out on the ground. Funeral goods included iron piece for starting fire, iron ring, buckle frame, and pincers, as well as six bronze plates from a belt set and an Abbasid dinar (753—754) probably plated with gold in antiquity. In a trench at Plaskyi Ravine burial ground, a classic Saltiv culture cache and a silver Khawarijian dirham of 179 AH (795—796) found in cultural layer at the site. The materials from caches find broad analogies in assemblages with cremations in the region. Numismatic finds discovered at burial grounds with cremations for the first time present chronologic datum points for dating the elements of belt sets. В научный оборот вводится информация о двух новых салтово-маяцких кремационных могильниках (Балка Сухая Гомольша и Яр Плоский), которые выявлены в Верхнем Подонцовье в Змиевском р-не Харьковской обл. Разведками полевых сезонов 2013 и 2016 гг. установлено, что оба могильника практически полностью уничтожены современными кладоискателями. Могильник Яр Плоский по размеру сопоставим с известным Сухогомольшанским кремационным могильником. Разведками также установлено, что последний памятник имеет свое продолжение и не может считаться полностью исследованным. Могильник Балка Сухая Гомольша минимум в десять раз превышает размеры выше упомянутого памятника. В шурфах 1 и 2 могильника Балка Сухая Гомольша выявлены тайник и безурновое погребение соответственно. Погребение прослеживалось пятном размером 0,75 × 0,35 м и фиксировалось на глубине 0,3 м от современной поверхности. Края погребальной ямы археологическими методами не прослеживались, что, вероятно, свидетельствует о том, что погребение совершено на древней дневной поверхности (кости и инвентарь просто были высыпаны на землю). В состав погребального инвентаря входили железные изделия: кресало, кольцо-рамка пряжки и пинцет, а также бронзовые: шесть бляшек поясной гарнитуры и Аббасидский динар 135 г. х. (753—754 гг.), вероятно, плакированный золотом в древности. В шурфе на могильнике Яр Плоский выявлен классический салтовский тайник и серебряный Кариджитский дирхем 179 г. х. (795—796 гг.), происходящий из культового слоя памятника. Материалы из тайников имеют широкие аналогии в кремационных комплексах региона. Впервые выявленные на кремационных могильниках нумизматические находки дают хронологические реперы в датировках элементов поясной гарнитуры.